2023
DOI: 10.1097/bpb.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Role of proximal tibiofibular fixation in leg lengthening with the Ilizarov method in the achondroplastic patient

Abstract: The role of proximal tibiofibular joint (TFJ) transfixion during Ilizarov tibial lengthening is still debated in the literature. The aim of this study was to show that TFJ transfixion can be avoided with no impact on patient outcome. All achondroplastic patients undergoing tibia lengthening from 1999 to 2018 were included. Patients were divided in two groups: group A (11 patients) submitted to proximal TFJ transfixion and group B (22 patients) not submitted to TFJ transfixion. The results showed a statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This is the first study regarding the use of a tether fixation of the proximal tibiofibular joint during tibial MILN lengthening, thus the discussion will focus on related literature addressing similar clinical scenarios. Numerous studies demonstrated distal migration of the fibular head during lengthening [ 7 14 ], with greater distance migrated consistently observed when the tibiofibular joint had no fixation [ 10 ]. However, Song et al [ 15 ] demonstrated that fibular migration could occur even if the joint is fixed with a tensioned wire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study regarding the use of a tether fixation of the proximal tibiofibular joint during tibial MILN lengthening, thus the discussion will focus on related literature addressing similar clinical scenarios. Numerous studies demonstrated distal migration of the fibular head during lengthening [ 7 14 ], with greater distance migrated consistently observed when the tibiofibular joint had no fixation [ 10 ]. However, Song et al [ 15 ] demonstrated that fibular migration could occur even if the joint is fixed with a tensioned wire.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal fibula migration can be associated with clinically meaningful symptoms. Boero et al demonstrated no association between proximal fibular migration up to 41 mm with worsening knee function or malalignment [ 10 ]. This may be due to the gradually elongated proximal tibiofibular joint capsule [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…57 In contrast to femoral lengthening with internal devices, Rovira Martí et al 57 confirmed that prophylactic intramedullary rodding should be considered to prevent regenerate re-fracture after femoral lengthening using external fixators in patients with achondroplasia. In tibial lengthening with Ilizarov fixator, Boero et al 58 measured proximal migration of the fibular head when proximal tibiofibular fixation was not performed as opposed to when it was performed. However, this did not lead to differences in the clinical-functional outcome of the knee, radiographic results, and quality of life.…”
Section: Achondroplasiamentioning
confidence: 99%
“…Balci et al evaluated the results of simultaneous lengthening compared with consecutive lengthening of the femur and tibia in 26 patients with achondroplasia and determined that, although the difference was not significant, simultaneous bilateral femoral and tibial lengthening resulted in a greater disturbance of physeal growth 23 . Boero et al analyzed functional and quality-of-life scores to assess the effect of fixation of the proximal tibiofibular joint during Ilizarov external fixator lengthening of the tibia in a cohort of patients with achondroplasia 24 . Despite a significant difference in the magnitude of migration of the proximal tibiofibular joint (9.2 mm for the fixation group compared with 21 mm for the non-fixation group), the functional and quality-of-life scores were not related to fixation of the proximal tibiofibular joint.…”
Section: Achondroplasiamentioning
confidence: 99%